Contribution to the Mesostigmata fauna of Slovenia (Acari: Mesostigmata: Zerconidae et Macrochelidae) - Ujvári, Zsolt (Acta entomologica slovenica (Ljubljana), 2009)
From the material collected on several locations in Slovenia, 7 species of zerconid and 4 species of macrochelid mites were identified. All of the Zerconidae and 2 of the Macrochelidae species are newly recorded for the country. Description of male Zerconella leitnerae Willmann, 1953, morphological notes on Prozercon tragardhi Halbert, 1923, original drawings ofsome newly recorded species and maps are given.
Keywords: entomologija; najdbe; Slovenia; Slovenija